Fusion of low-cost and light-weight sensor system for mobile flexible manipulator - Chang, Tai Kiang (2019)
There is a need for non-industrial robots such as in homecare and eldercare. Light-weight mobile robots preferred as compared to conventional fixed based robots as the former is safe, portable, convenient and economical to implement. Sensor system for light-weight mobile flexible manipulator is studied in this research.